The increase cash holdings of UK public firms - wang, liyan (2012)
There are lots of study show that cash holding of U.S. companies increased during the last two decades. However, there are only limited studies based on UK market. As there are some difference between US and UK corporate governance, which result in different ownership structure. So i expected UK public companies should hold more cash than US public companies. In this paper i mainly followed model Bates(2009) applied to investigate UK public companies cash holidngs.